2015
DOI: 10.1287/moor.2014.0684
|View full text |Cite
|
Sign up to set email alerts
|

From Cost Sharing Mechanisms to Online Selection Problems

Abstract: We consider a general class of online optimization problems, called online selection problems, where customers arrive sequentially, and one has to decide upon arrival whether to accept or reject each customer. If a customer is rejected, then a rejection cost is incurred. The accepted customers are served with minimum possible cost, either online or after all customers have arrived. The goal is to minimize the total production costs for the accepted customers plus the rejection costs for the rejected customers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In future research, the linkage of RM in attended home delivery to other existing streams should be made more transparent and eventually exploited, e.g., to online customer selection in supply chain management (e.g., Levi 2015, Elmachtoub andLevi 2016) or to dynamic vehicle routing (e.g., Bent andVan Hentenryck 2004,Ulmer et al 2018). For example, as a result of such an integrated study, research in same-day delivery could be pushed and streamlined.…”
Section: Attended Home Deliverymentioning
confidence: 99%
“…In future research, the linkage of RM in attended home delivery to other existing streams should be made more transparent and eventually exploited, e.g., to online customer selection in supply chain management (e.g., Levi 2015, Elmachtoub andLevi 2016) or to dynamic vehicle routing (e.g., Bent andVan Hentenryck 2004,Ulmer et al 2018). For example, as a result of such an integrated study, research in same-day delivery could be pushed and streamlined.…”
Section: Attended Home Deliverymentioning
confidence: 99%
“…Note that we assume the per unit rejection cost is uniform among customers. In Elmachtoub and Levi (2014), it is shown that if there are customer-specific rejection costs per unit, then no deterministic nor randomized online algorithm can have a constant competitive ratio.…”
Section: Economic Lot Sizing Problem With Online Customer Selectionmentioning
confidence: 99%
“…We now outline some of the related work in cost sharing in a dynamic shared resource allocation setting, in which our contributions can potentially discover alternate solutions with different desiderata. For instance, Elmachtoub and Levi (2014) study online allocation problems where customers arrive sequentially, and decisions regarding whether to accept or reject customers must be made upon their arrival, with the goal of minimizing the sum of production costs (for accepted customers) and rejection costs.…”
Section: Related Workmentioning
confidence: 99%